Public Relations: Investigating the Impact of Internal Public’s Engagement on Megaphoning and Scouting Behaviors - Khalid Bourrouk; Adiba Bousfiha; Adnane Mrabti (Garuda Prestasi Nusantara Consulting, 2023)
While previous studies in the literature have concentrated extensively on investigating employee engagement and communication behaviors in relation to other organizational variables, very little research has examined the association between the two constructs. Therefore, the present study aimed to address this deficiency in the literature of public relations by examining the effect of engagement on employee communication behaviors. Specifically, forms of engagement, including alignment, affective and action-orientation (Shrotryia and Dhanda, 2020) were posited as antecedents to Kim and Rhee’s (2011) two dimensions of employee communication behavior, namely megaphoning and scouting. Using non-probability snowball sampling, a total of three hundred and seventy eight Moroccan employees who currently work for Moroccan private organizations participated in the study by filling out a 20-item questionnaire. By deploying Pearson-product moment correlation and linear regression, all three dimensions of engagement were found to be significantly associated with employees’ megaphoning and scouting behaviors. The study highlights the critical role of enhancing cognitive, affective and behavioral engagement of employees in influencing megaphoning and scouting behaviors. Important implications of the findings are discussed. In addition, the study’s limitations and recommendations for future research are addressed.